2018
DOI: 10.1186/s12866-018-1295-4
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and Wolbachia-based multimarker approach for the rapid and accurate identification of tsetse species

Abstract: BackgroundTsetse flies (Diptera: Glossinidae) are solely responsible for the transmission of African trypanosomes, causative agents of sleeping sickness in humans and nagana in livestock. Due to the lack of efficient vaccines and the emergence of drug resistance, vector control approaches such as the sterile insect technique (SIT), remain the most effective way to control disease. SIT is a species-specific approach and therefore requires accurate identification of natural pest populations at the species level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…We amplified partial sequences of ITS1 using primers Glossina_ITS1_for and Glossina_ITS1_rev (Dyer et al, ), following the protocol described in this paper. For G. pallidipes , the ITS1 PCR product should display a length of around 919 bp, while G. brevipalpis and G. swynnertoni are expected to display the G. morsitans profile (~775 bp) (Augustinos et al, ). This was used on a selected subset of G. pallidipes to check for agreement with species determination (see Results).…”
Section: Methodsmentioning
confidence: 99%
“…We amplified partial sequences of ITS1 using primers Glossina_ITS1_for and Glossina_ITS1_rev (Dyer et al, ), following the protocol described in this paper. For G. pallidipes , the ITS1 PCR product should display a length of around 919 bp, while G. brevipalpis and G. swynnertoni are expected to display the G. morsitans profile (~775 bp) (Augustinos et al, ). This was used on a selected subset of G. pallidipes to check for agreement with species determination (see Results).…”
Section: Methodsmentioning
confidence: 99%
“…These results are consistent with previous studies that reported a misidentification of wild tsetse species (particularly, G. palpalis palpalis , G. palpalis gambiensis , G. tachinoides and G. morsitans submorsitans ). They suggest that the morphological characters alone are not sufficient for accurate identification of tsetse fly species (Augustinos et al, 2018; Dyer et al, 2008). The ITS1 length polymorphism detected on a polyacrylamide gel was enough to differentiate the species studied.…”
Section: Discussionmentioning
confidence: 99%
“…Although morphological characteristics allowed the classification of 31 tsetse species into three distinct groups, it remains very difficult to clearly distinguish some tsetse species from the same group (Augustinos et al, 2018). For instance, G. palpalis palpalis , G. tachinoides and G. fuscipes not only share identical morphological characteristics but also can be in sympatry in some bio‐ecological settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Wolbachia genome sequences were also found in the genome of G. austeni , which also contains an active cytoplasmic Wolbachia infection [ 175 ]. It is worth noting that the presence of chromosomal and cytoplasmic Wolbachia gene sequences together with a nuclear marker (internal transcribed spacer 1, ITS1) allowed us to develop a quick, effective and robust protocol for the accurate identification of several tsetse species and subspecies, irrespectively of their origin (field, laboratory or museum specimens) (accessed on 10 February 2021) [ 176 ].…”
Section: Main Research Achievements—livestock Pestsmentioning
confidence: 99%